PI3K/Akt in IPF: untangling fibrosis and charting therapies - Bhatt, Janki; Ghigo, Alessandra; Hirsch, Emilio (Frontiers in Immunology, 2025)
Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive lung disease characterized by abnormal epithelial repair, persistent inflammation, and excessive extracellular matrix deposition, leading to irreversible scarring and respiratory failure. Central to its pathogenesis is the dysregulation of the PI3K/Akt signaling pathway, which drives fibroblast activation, epithelial-mesenchymal transition, apoptosis resistance, and cellular senescence. Senescent cells contribute to fibrosis through the secretion of pro-inflammatory and profibrotic factors in the senescence-associated secretory phenotype (SASP). Current antifibrotic therapies, Nintedanib and Pirfenidone, only slow disease progression and are limited by side effects, highlighting the need for novel treatments. This review focuses on the role of PI3K/Akt signaling in IPF pathogenesis, its intersection with inflammation and fibrosis, and emerging therapeutic approaches targeting molecules along this pathway.